Effective strategies for isolating DNA from members of Asteraceae with high concentrations of secondary metabolites - Bailey, Dustin W.; Attia, Ziv; Reinert, Stephan; Hulke, Brent S.; Kane, Nolan C. (Biotechniques, 2022)
METHOD SUMMARY A protocol for obtaining high-quality DNA extracted from plant tissue of species known to have interfering secondary metabolites is described.
CRIS-Team WoS Importer:2022-02-18